Preliminary study on the impact of flow rate and sediment load to the geometry formation of meanders in a meandering river / Noor Safwan Muhamad, Junaidah Ariffin and Zulhafizal Othman - Muhamad, Noor Safwan; Ariffin, Junaidah; Othman, Zulhafizal (2013)
This study demonstrates the development of meanders with respect to different flow rate and sediment load The knowledge on meanders is important. not only because it changes the geometry of the river but it also can cause threats to the people and properties. With more than 150 rivers throughout Malaysia. the knowledge on meander behavior is vital to avoid problems associated with poor planning of the development at riverside. Eight sets of experiments have been conducted using Armfield S12 MKll Advanced Hydrology Study System at the Faculty of Engineering. UNISEL Bestari Jaya Campus. The experiments was conducted under controlled environment with flow rate and sediment load as the variable parameters while the other factors that can affect meander growth and migration are kept constant. The changes in cross section were measured and 3D surface was generated using Surfer 9 to analyze the effect of variation in flow rate and sediment load to the erosion. transportation and deposition processes that involved in meander meander growth and migration. The relationship between flow rate and sediment load with the migration and growth pattern of meanders are discussed well in this paper. This study is meant to be continued further to come out with suitable equations in predicting meander migration